Proposta de procedimento para projeto de controladores fuzzy multivariáveis - Vasconcellos, Brunna Santana de (2017)
Control’s practical problems usually appear with lots of variables to be controlled simultaneously. Its biggest problem is that frequently the variables depend on each other, making necessary a deep study about multivariable control systems. Analyze capability and potential of different control strategies is extremely important to get the most appropriate control mode to the system. In this context, this work approaches systematic procedures to project an effective fuzzy controller focused in multivariable systems. It consists in splitting the controller design in three steps, where it’s parameters are synchronized with multivariable fuzzy controllers. The first step considers a system with a single input and a single output. At second step, all the controllers are joined into a single one, with all the inputs and outputs include without accounting each loop influence’s. Last step happens including the influence of each loop on the whole system. This approach makes possible a better performance from the controller, since it’s possible to analyze the system behavior in each step. To prove this procedure efficiency, the method is applied to different cases of study, including practical and simulated cases. The outcome multivariable fuzzy controller is compared with others by using graphical analysis and calculated indexes of performance to validate the chosen procedure.